Mental Health Literacy from the Marind Perspective - Saya, Prisca; Novianty, Anita (International Dialogues on Education Journal, 2022)
This study aims to describe mental health literacy components from the perspective of the Marind people in Merauke Papua, Indonesia. The participants of this study consisted of 197 Marind people (110 men and 87 women), ranging from 12-71 years old. The method used was a survey of distributed questionnaires consisting of consent sheets, demographic data, and several open questions based on the vignette of Schizophrenia and Major Depression designed by researchers based on the conceptual framework of Jorm (2000). Data were analyzed with descriptive statistics. Participant responses were categorized into several themes according to the concept of mental health literacy. The results showed that most of the participants' responses were different from the biomedical framework in terms of symptom recognition, belief in the cause of mental disorders, and the way to seek help. Culture-based beliefs contribute greatly to the understanding of mental illness symptoms. The implications of this research can be used as an academic reference as consideration for the provision of community-based interventions that are sensitive to the culture.